Destination Image, Attractions, and Promotion as Behavioural Drivers of Tourist Visit Intention - Anggraeni, Melda; Lestari Zainal Ridho, Sari (Inovasi Analisis Data, 2025)
Purpose: The present study explores how destination image, tourist attractions and promotion mutually influence proving the intent to visit tourists in a context of cultural heritage tourism. Considering the transformation of behavioural dynamics in tourism toward experience-motivated behaviour, it is crucial to understand the interaction among these three factors in order to enhance destination competitiveness.Method: Data were assessed using multiple regressions to test partial and full effects of the predictors on visit intention. Measurement items were modified from existing scales to establish construct validity and reliability.Findings: Findings show visitor attractions as the primary driver of visit intention, evidencing an ever-growing prominence of experiential value over cognitive evaluation. Destination image and promotion exert weak influences from a stand-alone perspective, but they play a significant role when considered jointly, suggesting that intention formation is multidimensional and is driven by interaction effects rather than the influence of single variables.Novelty: The research develops an expanded model of integrated behaviour in which experiential attraction quality, placing it as the most significant antecedent of intention, and the destination image and promotion are interdependent forces, not independent ones. This adds an enhanced insight about intention formation in heritage tourism settings as the sensory submersion and cultural authenticity outweigh conventional promotional prompts.Implications: The results offer destination managers strategic insights, indicating that attention should focus on the development of attractions, coherence in their natural attractiveness and a match between building up the image messages and the actual experiential attributes. Inclusive marketing strategies based in reality are suggested to maintain visitors’ engagement and behavioural intention.